Assessing the Potential of Prambanan Biodiversity Park for Sustainable Food Resources and Agriculture in Kemudo, Klaten, Central Java - Bimantio, Mohammad Prasanto; Ferhat, Amallia; Putra, Dian Pratama; Nugraha, Nanda Satya; Ayu, Indah Kusuma; Suendra, Akhta (Universitas Atma Jaya Yogyakarta, 2024)
Prambanan Biodiversity Park (TKP), Klaten, Central Java, is an important natural reserve for preservation of local biodiversity and environmental protection by PT.Sarihusada Generasi Mahardhika. This research investigates the park's potential in providing food resources and supporting agricultural practices for nearby communities through plant species identification including ecological relationships between species and plants that contribute to pest control in agricultural systems. The collected data provides an overview of the park's biodiversity and serves as a baseline for further analysis. The research finds several potential benefits of utilizing TKP for food resources and agriculture. The diverse flora of the park offers a variety of edible plants, such as Moringa oleifera and fruit-based species, which can enhance local diets and provide nutritional diversity. Furthermore, traditional plants like mojo hold potential as natural pesticides, contributing to pest control in agricultural fields. The research recommends the development of conservation strategies and policies focused on sustainable practices, community participation, and educational initiatives to maximize the potential benefits. TKP emerges as an invaluable resource capable of supplying essential food provisions and supporting eco-friendly agricultural practices for neighboring communities, thereby emphasizing the criticality of interweaving biodiversity preservation within the framework of local food systems.